2020
DOI: 10.1002/nem.2106
|View full text |Cite
|
Sign up to set email alerts
|

Bitcoin's dynamic peer‐to‐peer topology

Abstract: Summary Topology discovery is a prerequisite when investigating the network properties; with the enormous number of Bitcoin users and performance issues, it becomes critical to analyse the network in a fashion that makes it possible to detect all Bitcoin's nodes and understand their behaviour. In massive, dynamic, and distributed peer‐to‐peer (P2P) networks like Bitcoin, where thousands of updates occur per second, it is hard to obtain an accurate topology representing the structure of the network as a graph w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…In 2018, Deshpande et al [20] and in 2020, Essaid et al [31] presented a similar technique to infer the topology. They developped an emulator and emulated a probable topology of the network but not the real one.…”
Section: A Previous Attemptsmentioning
confidence: 99%
“…In 2018, Deshpande et al [20] and in 2020, Essaid et al [31] presented a similar technique to infer the topology. They developped an emulator and emulated a probable topology of the network but not the real one.…”
Section: A Previous Attemptsmentioning
confidence: 99%
“…The number of created connections maintained by new nodes is often fixed in the client source code. Examples of this construction are the network of Bitcoin [20] and classic Gnutella [6].…”
Section: Network and Graphsmentioning
confidence: 99%
“…3 In recent years, several researchers tried to reveal the Bitcoin network. 28,29 Miller et al first analyzed the topology of the real Bitcoin network by using the method called AddressProve. 28 They confirmed that most nodes had degrees in the range of 8-12, which were close to the maximum number of outgoing connections.…”
Section: Bitcoin Networkmentioning
confidence: 99%
“…Because of the security and anonymity concerns, the Bitcoin system intentionally aims to conceal the structure of the Bitcoin network 3 . In recent years, several researchers tried to reveal the Bitcoin network 28,29 . Miller et al first analyzed the topology of the real Bitcoin network by using the method called AddressProve 28 .…”
Section: Block Diffusion Over Bitcoin Networkmentioning
confidence: 99%